Prarancangan Pabrik Isobutilena dari Tersier Butil Alkohol dengan Proses Dehidrasi menggunakan Katalis Styrene-Divinylbenzene Kapasitas 15.000 Ton/Tahun - Santoso, Widhyoko Heri; , M. Mujiburohman,S.T., M.T., Ph.D; , Ir. Herry Purnama, M.T., Ph.D (2016)
Isobutylene or 2-methyl propene has the molecular formula C4H8, usually produced as a by product of the petroleum refining process. This compound serves as raw material for the manufacture of methyl tertiary butyl ether (MTBE) and ethyl tertiary butyl ether (ETBE) are useful to increase the octane number fuel. Isobutylene polymerization reaction can produce synthetic rubber (butyl rubber). Isobutylene reacted with phenol to form the antioxidant butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA). Due to increasing needs of isobutylene and reduce imports as well as for the ASEAN free market competition (MEA). Some factors to consider include aspects of the supply of raw materials, labor, transportation, utilities and marketing. Then the factory strategic location is in the area of Industrial Tuban, East Java, Indonesia in 2019 on a land area of 22.675 m2 and employe 159 people. In the process of making isobutylene done dehydration reaction of tertiary butyl alcohol (TBA) is aided by a catalyst in the styrene-divinyl benzene flow stirred tank reactor (RATB). Dehydration reaction is endothermic reaction and reversible conditioned towards products with operating temperature of 93°C and a pressure of 5 atm. The reactor used is isothermal that operates continuously. The results of factory production of isobutylene 1893,754 Kg/h, raw material requirements TBA 2966,654 Kg/h and the catalyst of 383,897 Kg. The results of the economic analysis of the obtained isobutylene plant prarancangan fixed capital investment (FCI) of Rp354.623.090.728,00 and working capital (WC) Rp231.693.692.096,00. Feasibility analysis results obtained from the return on investment (ROI) before tax after tax 34,71% and 24,30%. Pay Out Time (POT) before tax and after-tax 2,24 tahun of 2,92 years. Break Even Point (BEP) 47,91%, Shut Down Point (SDP) of 29,91% and a Discounted Cash Flow (DCF) of 30,28%. The results of the economic analysis concluded that the plant isobutylene from TBA with the dehydration process capacity of 15.000 ton/year feasible to set.